Developing Indicators To Measure Health Care Performance By Prof. Dr David Schwappach, Institute Of Social And Preventive Medicine (ISPM) University Of Bern - Schwappach, David (My University, 2023)
To develop indicators to measure health care performance, it is important to: accept the pain of reduction a complex world to simple metrics; mind the consequences adaption to indicators may have; resist to make indicators overly complex; and choose sensitive-to-differences indicators and take a learning-oriented process.
Keywords: evaluation; healthcare performance; indicators